Characteristics of Managing Operational Banking Risk - Leonardo Badea; Adela Socol (Theoretical and Applied Economics, 2008)

(untitled)
The objective of this paper is to provide a global perspective of the operational risk from a banking societies’ viewpoint. We describe the main regulations and settlements in the field and examine the various approaches of the operational banking risk. The paper presents the need of banks to managing operational risk. We study comparatively for a banking society the capital charge for covering the operational risk under the basic indicator approach and under the standardized approach. We present a case study of implementing current capital requirements at the level of a Romanian banking society. From the theoretical approach and from the description of quantifying of operational banking risk, the results of this study insist on the importance of measuring of operational banking risk and identifies major issues that need to be considered to improve the managing operational banking risk.